New literature in the field of speech development: Ljiljana Kelemen Milojević: Speech development in a preschool institution, third supplemented and amended edition, Preschool Teacher Training College "Mihailo Palov", Vršac, 2021. - Đorđev, Ivana Đ. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2022)
_